Teachers’ Reflective Journals as Professional Narratives: Insights into Pedagogical Ethics and Practice - Markus Oci; Luis Santos; Andres Villanueva; Ali Khan (International Journal of Educational Narratives, 2025)
Background. Reflective practice has long been recognized as a cornerstone of teachers’ professional growth, offering a pathway for ethical awareness and pedagogical refinement. This study explores teachers’ reflective journals as professional narratives that reveal the moral, emotional, and intellectual dimensions of teaching. Purpose. The purpose of this research is to analyze how reflective writing fosters teachers’ ethical consciousness, self-understanding, and pedagogical decision-making within the context of daily classroom practice. Method. Using a qualitative narrative inquiry design, data were collected from 20 reflective journals written by in-service teachers over one academic semester. Results. The findings demonstrate that reflective journals function not merely as records of experience but as dialogical spaces for reconstructing professional identity and moral integrity. Teachers’ reflections revealed an ongoing interplay between personal values and institutional expectations, highlighting the ethical complexity of teaching.   Conclusion. The study concludes that reflective journaling cultivates moral sensitivity, critical awareness, and a sustained commitment to ethical teaching practice, positioning it as a vital narrative tool for professional learning.